Schoology: una herramienta para el desarrollo de la habilidad escrita en inglés - Rodríguez Tamayo, Ilba Yaneth; Vargas Hernández, Leidy Jhoanna (Colombian Applied Linguistics Journal, 2020)
This study is the result of a research carried out in a Master’s Program. It deals with the relationship between the development of the written skill of the English language and the implementation of the LMS Schoology platform— as a tool for this purpose— in a group of elementary school students in a private institution in Tunja, Colombia. Data was collected by using students’ artifacts, a questionnaire, and a focus group, which information was analyzed carefully. At the end, it is evident the way in which the platform Schoology contributed positively to the writing skill development, throughout the integration of factors like the motivation, the proposal of attractive activities and the development of tasks inside the classroom as well as outside it. Likewise, the students showed acceptance of the system and their willingness to learn improved.